Prevalence of and Trends in the Co-Existence of Obesogenic Behaviors in Adolescents From 15 Countries - Fan, Hui; Zhang, Xingyu (Frontiers in Pediatrics, 2021)
Background: The global epidemic of pediatric obesity is well known, but data on co-existence of obesogenic behaviors are limited. We aim to report the prevalence of and trends in the co-existence of obesogenic behaviors in adolescents from 15 countries. Methods: This study was based on the Global School-based Student Health Survey 2003–2017 and included 121963 adolescents aged 12–15 years from 15 countries where at least 2 cross-sectional surveys were conducted. We used sampling weights and calculated the country-level prevalence of and trends in the co-existence of obesogenic behaviors (low fruit and vegetable intake, anxiety-induced insomnia, no physical activity, and sedentary behavior) during survey years. Pooled prevalence and trend estimates were calculated with random-effects models. Results: Pooled prevalence of exposure ≥ 1, ≥2, and ≥3 obesogenic behaviors was 88.2%, 44.9%, and 9.8% in the first survey and 88.4%, 46.4%, and 10.2% in the last survey, respectively. Plateauing, increasing, and decreasing trends in the co-existence of obesogenic behaviors were observed in different countries. Specifically, we identified a plateauing pooled trend in the exposure ≥ 1, ≥2, and ≥3 obesogenic behaviors [odds ratios (95% confidence intervals): 1.03 (0.93, 1.14), 1.05 (0.97, 1.13), and 1.06 (0.95, 1.18), respectively]. Conclusion: Trends in the prevalence of the co-existence of obesogenic behaviors varied significantly across different countries, but the prevalence remained high in most countries. These findings suggest the need for behavioral interventions to mitigate obesogenic behaviors in adolescents for overweight and obesity prevention.